A shark's eye view: testing the 'mistaken identity theory' behind shark bites on humans. Issue 183 (27th October 2021) - Ryan, Laura A.; Slip, David J.; Chapuis, Lucille; Collin, Shaun P.; Gennari, Enrico; Hemmi, Jan M.; How, Martin J.; Huveneers, Charlie; Peddemors, Victor M.; Tosetto, Louise; Hart, Nathan S.
Abstract : Shark bites on humans are rare but are sufficiently frequent to generate substantial public concern, which typically leads to measures to reduce their frequency. Unfortunately, we understand little about why sharks bite humans. One theory for bites occurring at the surface, e.g. on surfers, is that of mistaken identity, whereby sharks mistake humans for their typical prey (pinnipeds in the case of white sharks). This study tests the mistaken identity theory by comparing video footage of pinnipeds, humans swimming and humans paddling surfboards, from the perspective of a white shark viewing these objects from below. Videos were processed to reflect how a shark's retina would detect the visual motion and shape cues. Motion cues of humans swimming, humans paddling surfboards and pinnipeds swimming did not differ significantly. The shape of paddled surfboards and human swimmers was also similar to that of pinnipeds with their flippers abducted. The difference in shape between pinnipeds with abducted versus adducted flippers was bigger than between pinnipeds with flippers abducted and surfboards or human swimmers. From the perspective of a white shark, therefore, neither visual motion nor shape cues allow an unequivocal visual distinction between pinnipeds and humans, supporting the mistaken identity theory behind some bites.